Electrospun polyvinylidene fluoride (pvdf) blended with cellulose nanocrystals (cncs) as piezoelectric material - Aminatul Sobirah, Zahari; Muhammad Hafiz, Mazwir; Izan Izwan, Misnon (2021)
PVDF is a semi-crystalline polymer. Excellent thermal stability, light weight, high flexibility Sensors, actuators, transducers, energy storage, energy harvesting. Three main crystalline phases (α,β and γ) β-phase of PVDF give rise to a piezoelectric constant (electroactive state). Incorporating CNCs into PVDF to improve mechanical and electrical properties.